2021
DOI: 10.1016/j.heliyon.2021.e06307
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular profiles of anterior nervous system regeneration in Diopatra claparedii Grube, 1878 (Annelida, Polychaeta)

Abstract: The polychaete Diopatra claparedii Grube, 1878 is among those organisms successfully carrying out full body regeneration, including the whole nervous system. Thus, D. claparedii potentially can be regarded for the nervous system regeneration (NSR) study. However, data on the property of its nervous system and the NSR profile are still lacking. In this study, we investigated the morphology of D. claparedii anterior nervous system (ANS) and examined the cellular and molecular profiles on its early anterior NSR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 38 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Our investigation supports that polychaetes from the genus Diopatra have a complete and advanced nervous system that leads to their special ability to regenerate the nervous system (Pires et al, 2012;Pires et al, 2016;Nazri et al, 2021). This understanding might be beneficial to be applied in medicine as an animal model.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Our investigation supports that polychaetes from the genus Diopatra have a complete and advanced nervous system that leads to their special ability to regenerate the nervous system (Pires et al, 2012;Pires et al, 2016;Nazri et al, 2021). This understanding might be beneficial to be applied in medicine as an animal model.…”
Section: Discussionsupporting
confidence: 79%
“…Beckers et al (2019) reported that the anterior CNS consists of a dorsal prostomial brain with several commissures and connectives connecting to the ventral nerve cord. Other than that, D. claparedii has also been reported to possess those characteristics based on the study conducted by Nazri et al (2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations